Mapping Design for Innovation Policy in Wales and Scotland. (2nd January 2017) - Whicher, Anna; Walters, Andrew
Abstract: In 2014, design featured in 15 of the 28 European Member States' innovation policies. Design strategies were in operation in Denmark, Estonia, Finland, France and Latvia. The European Commission has also developed an Action Plan for Design-driven Innovation. While design is gathering momentum as a driver of innovation in EU and national policy, there is a gap at regional levels. In Wales and Scotland there is infrastructure to support enterprises to use design, so arguably there is an opportunity for them to lead the regional design policy agenda in Europe. However, this raises the question of how to develop effective policies for design. Innovation policy is based on analysis of the Innovation Ecosystem; can the concept of Design Innovation Ecosystems be useful for design policy development? Through four Design Policy Workshops and surveys in Wales and Scotland, this paper presents the concept of Design Innovation Ecosystems as an approach to inform policymaking for design-driven innovation.